A New Gauge Mechanism for Massive Gauge Bosons - Duc, Dao Vong (Communications in Physics, 2011)
We propose a new mechanism for creating the mass of gauge bosons independently of Higgs mechanism. The main idea is to introduce some scalar function of space-time coordinates in the gauge transformation with some appropriate constraints. The model also allows the possibility for the gauge coupling to be changed in space-time.